MATHEMATICS SKILL OF FIFTEEN YEARS OLD STUDENTS IN YOGYAKARTA IN SOLVING PROBLEMS LIKE PISA - Nidya Ferry Wulandari; Jailani Jailani (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
The aims of this research were to describe mathematics skill of 8th fifteen-year old students in Yogyakarta in solving problem of PISA. The sampling was combination of stratified and cluster random sampling. The sample consisting of 400 students was selected from fifteen schools. The data collection was by tests. The research finding revealed that mathematics skill of fifteen-year old students in Yogyakarta in solving problem of PISA was low in category but it was better than Indonesian students in PISA 2012. Mathematics skill of fifteen-year old students in Yogyakarta in solving problem of PISA was below the OECD average of PISA 2012.DOI: http://dx.doi.org/10.22342/jme.9.1.4231.129-144